Pendidkan Islam di Era Globalisasi - Andri Afriani (LP2M STAI Darul Kamal NW Lombok Timur, 2020)
In the globalization era, Islamic education must prepare a strategy in meeting the challenges of globalization which is very complex. To deal with such problems, there are some innovative steps in the form of changing the vision, mission and goals. Integrating the approach model and learning method that combines a behaviorism approach with a constructive approach that is godly valid. Using management that combines systems and infrastructure approaches with approaches that are valid in human behavior. By reintroducing the vision and mission and objectives of Islamic education in a comprehensive manner. This is important to do, because so far the world community has not known Islamic education as a whole and transparently. The impact of globalization that already exists before us various kinds of models there are 'positive' for easy living, comfortable, cheap, beautiful, advanced. There is also a negative impact that is causing anxiety, suffering and misdirection. Whereas Islamic Education is an Islamic-based education and is a system that has several interrelated components, for example the aqeedah, shari'ah and moral system which includes the effective, cognitive, and psychomotor domains, to prepare humans to live perfectly and happily.